Early circulating levels of endothelial cell activation markers in aneurysmal subarachnoid haemorrhage: associations with cerebral ischaemic events and outcome. Issue 1 (16th December 2005) - Frijns, C J M; Fijnheer, R; Algra, A; van Mourik, J A; van Gijn, J; Rinkel, G J E
Abstract : Objective: To investigate the relation of endothelial cell activation with delayed cerebral ischaemia (DCI) and outcome after subarachnoid haemorrhage (SAH). Methods: Concentrations of soluble (s) intercellular adhesion molecule-1, sE-selectin, sP-selectin, ED1-fibronectin, von Willebrand Factor (vWf), and vWf propeptide were measured within three days of SAH onset. The associations with poor outcome were investigated at three months in 106 patients. In 90 patients in whom the occurrence of cerebral ischaemia could be dated accurately, two analyses were undertaken: one for all ischaemic events (n = 32), including those related to treatment, and another for spontaneous DCI (n = 11). Concentrations of markers were dichotomised at their medians. The associations of endothelial cell activation markers with outcome were expressed as odds ratios (OR) from logistic regression and those with ischaemic events as hazard ratios (HR) derived from Cox regression. Results: Early vWf concentrations were associated with poor outcome (crude OR = 4.6 (95% CI, 2.0 to 10.9; adjusted OR = 3.3 (1.1 to 9.8). Early levels of vWf were also positively related to occurrence of all ischaemic events (crude HR = 2.3 (1.1 to 4.9); adjusted HR = 1.8 (0.8 to 3.9) and with occurrence of spontaneous DCI (crude HR = 3.5 (0.9 to 13.1); adjusted HR = 2.2 (0.5 to 9.8). None of the other markers showed any associations. Conclusions: Concentrations of sICAM-1, sP-selectin, sE-selectin, and ED1-fibronectin do not predict the occurrence of DCI or outcome. The positive associations of raised early vWf concentrations with ischaemic events and poor outcome after SAH may reflect a predisposition to further ischaemic injury through formation of microthrombi in the cerebral circulation.